2018
DOI: 10.1111/jopy.12369
|View full text |Cite
|
Sign up to set email alerts
|

Fitting motivational content and process: A systematic investigation of fit between value framing and self‐regulation

Abstract: Our findings provide first insights into the psychological process of person-value framing fit affecting value endorsement. We discuss implications for cross-cultural value research and research on value-congruent behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
1
7
0
Order By: Relevance
“…Evolutionary theory suggests infectious disease may have an especially high likelihood to induce behavioral, and thus value, adaptation (Thornhill & Fincher, 2014). Such disease is likely to induce collective behavioral reactions that reduce disease spread by activating behavioral avoidance systems that are compatible with conservation values (e.g., Woltin & Bardi, 2018). This activation decreases out-group contact, openness to novel experiences, and self-directed thought and action (Schaller, 2015).…”
mentioning
confidence: 99%
“…Evolutionary theory suggests infectious disease may have an especially high likelihood to induce behavioral, and thus value, adaptation (Thornhill & Fincher, 2014). Such disease is likely to induce collective behavioral reactions that reduce disease spread by activating behavioral avoidance systems that are compatible with conservation values (e.g., Woltin & Bardi, 2018). This activation decreases out-group contact, openness to novel experiences, and self-directed thought and action (Schaller, 2015).…”
mentioning
confidence: 99%
“…Recently, a lot of international studies have been published on the topic of the individual's values and axiological orientations. They include studies of individual personality values and the paradigm of motivational goal of axiological orientations and universal basic human values [1,7]; studies related to revealing the connection between individual personality values and professional values [8]; the relation between values and individual's anxiety [9]; the relation between value and aggressiveness [10]; the relation between values and subjective well-being [11]; the relation between values and behavior [12,13]; the relation between values and personality traits [14]; study of correspondence between axiological orientations and self-regulation [15]; study of axiological orientations in children [16]; study of axiological orientations and analysis of their changes during the entire lifespan [17], and others. Russian psychological and pedagogical literature presents theoretical predispositions for solving the problem of increasing the efficiency of the professional-axiological orientations development in prospective teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, people may naturally conceptualize nature values as a desired goal they wish to approach, rendering promotion-framed messages more fitting. Indeed, previous research found stronger endorsement of approach-than avoidance-framed values among promotion focused participants, whereas value-framing did not impact value endorsement among prevention focused participants (Woltin & Bardi, 2018). Second, regardless of values, asymmetrical regulatory fit effects emerged in a recent meta-analysis, showing that promotion fit had stronger effects on evaluations than prevention fit (Motyka et al, 2014).…”
Section: The Current Researchmentioning
confidence: 91%
“…Participants' overall nature values score (M = 0.08, SD = 0.33) was computed as the mean score of the two relevant BWV-R items, universalism-animals ("Caring for the welfare of all animals") and universalism-nature ("Protecting the natural environment from destruction or pollution"), r(557) = .44, p < .001. As these two items are phrased in terms of nurturance (fitting promotion concerns) and protection (fitting prevention concerns), respectively, and in light of recent work on framing of human values and subsequent endorsement and value dimensionality (Aavik & Dobewall, 2017;Woltin & Bardi, 2018), it may be of interest that promotion focus was positively associated with the universalism-nature item, r(557) = .12, p = .006, and thus protection concerns. Correlations between promotion focus and the universalism-animals item, and correlations of both items with prevention focus were not significant (all rs < |.08|, all ps > .074).…”
Section: Procedures and Materialsmentioning
confidence: 99%